Hubungan Pengetahuan dan Sikap Ibu Tentang Speech Delay Pada Perkembangan Bahasa Anak Usia Toddler - Sipahutar, Angelina Victoria; Putri, Syeptri Agiani; Indriati, Ganis (Universitas Pahlawan Tuanku Tambusai, 2024)
Speech delay in children is a condition caused by a lack of verbal stimulation, social interaction, and environmental influence. Mothers' knowledge and attitudes play a crucial role in detecting and preventing this issue, which can affect children's language development in the future. This study aims to determine the relationship between mothers' knowledge and attitudes about preventing speech delay and the language development of toddlers. This research is a quantitative study using a descriptive correlational design with a cross-sectional approach. The sample consisted of 78 mothers with toddlers selected using a non-probability sampling technique with a purposive sampling method. All respondents completed questionnaires related to their knowledge and attitudes about preventing speech delay, and their children's language development was measured using the Early Language Milestone Scale 2 (ELMS-2). Data analysis was conducted using the chi-square test. The results showed that 73% of respondents were aged 26-35 years, 45% had completed high school, and 56% of mothers had sufficient knowledge. Additionally, 72% of respondents had a positive attitude, and 78% of children's language development was categorized as appropriate. The chi-square test showed a significant relationship between mothers' knowledge and children's language development (p-value = 0.000 < alpha 0.05), as well as between mothers' attitudes and children's language development (p-value = 0.000 < alpha 0.05). The conclusion of this study is that mothers' knowledge and attitudes about preventing speech delay are significantly related to the language development of toddlers. Therefore, educational programs on stimulating children's language development need to be enhanced.